Bioactive Potential of Dendrocalamus asper (Betung Bamboo Shoot) Against Colorectal Cancer: A Scoping Review of Preclinical Mechanisms and Research Gaps - Arie Jefry Ka'arayeno; Errick Endra Cita (Majalah Kesehatan Indonesia, 2026)
Colorectal cancer is one of the leading causes of morbidity and mortality globally. Bamboo shoots (Dendrocalamus asper) are known to contain dietary fiber, polyphenols, flavonoids, phytosterols, and oligosaccharides that have the potential to provide biological effects on the prevention of colorectal cancer. This study aims to map the latest scientific evidence regarding the bioactive content of D. asper, the mechanism of action relevant to colorectal cancer, and its opportunities for use as a candidate for phytopharmaceuticals and complementary therapies. This study is a scoping review with a systematic search approach. Literature searches were conducted on PubMed, ScienceDirect, SpringerLink, Google Scholar, and Garuda with a publication period of January 2018-August 2025. The selection of articles follows the inclusion-exclusion criteria and PRISMA guidelines. A total of 9 articles met the criteria and were analyzed through thematic synthesis. The results of the study showed that D. asper has an important phytochemical profile, including phenolics, flavonoids, and phytosterols that play a role in antioxidant, antiproliferative, anti-inflammatory, and apoptotic induced activity. Bamboo fiber and oligosaccharides have also been shown to promote beneficial bacterial growth and the production of short-chain fatty acids (SCFAs), specifically butyrates, which protect the colon mucosa and lower the risk of preneoplastic lesion formation. In vitro and in vivo evidence consistently supports bamboo's potential as a colorectal cancer prevention agent, although human clinical trials are not yet available. The conclusion of this study is that bamboo shoots show strong prospects as well as a candidate for phytopharmaceuticals as well as complementary therapies in efforts to prevent colorectal cancer.